First-principles simulation of neutral and charged oxygen vacancies in m-ZrO2: an origin of filamentary type resistive switching. (20th August 2022) - Chaurasiya, Rajneesh; Lin, Pei-En; Lyu, Cheng-Han; Chen, Kuan-Ting; Shih, Li-Chung; Chen, Jen-Sue
Abstract: Metal oxide ZrO2 has been widely explored for resistive switching application due to excellent properties like high ON/OFF ratio, superior data retention, and low operating voltage. However, the conduction mechanism at the atomistic level is still under debate. Therefore, we have performed comprehensive insights into the role of neutral and charged oxygen vacancies in conduction filament (CF) formation and rupture, which are demonstrated using the atomistic simulation based on density functional theory (DFT). Formation energy demonstrated that the fourfold coordinated oxygen vacancy is more stable. In addition, the electronic properties of the defect included supercell confirm the improvement in electrical conductivity due to the presence of additional energy states near Fermi energy. The CF formation and rupture using threefold and fourfold oxygen vacancies are demonstrated through cohesive energy, electron localization function, and band structure. Cohesive energy analysis confirms the cohesive nature of neutral oxygen vacancies while the isolated behavior for +2 charged oxygen vacancies in the CF. In addition, nudged elastic band calculation is also performed to analyze the oxygen vacancy diffusion energy under different paths. Moreover, we have computed the diffusion coefficient and drift velocity of oxygen vacancies to understand the CF. This DFT study described detailed insight into filamentary type resistive switching observed in the experimentally fabricated device. Therefore, this fundamental study provides the platform to explore the switching mechanism of other oxide materials used for memristor device application.